THE INFLUENCES OF PROMOTION MIX ON THE PURCHASE DECISION OF DAIHATSU XENIA CAR AT PT. ASTRA DAIHATSU INTERNATIONAL TBK PALEMBANG - Delly Marda T; Zakaria Wahab; Dian Eka; Marlina Widiyanti (President University, 2021)
Technological advances are currently developing very rapidly, Technological developments require companies to be able to adapt to follow technological advances. Automotive is one of the largest industries in Indonesia today. This industry contributes to trillions of rupiah in national income every year and creates jobs for thousands of our workers. The purpose of this research to determine how the influence of the promotional mix consisting of personal selling, sales promotion, advertising, direct marketing and public relations on the purchase decision of Daihatsu xenia at PT. Astra Daihatsu international Tbk Palembang. The data was collected through the dissemination of questionnaires to 100 respondents. This research data was analyzed using multiple linear regression analysis as well as t test and F test. The results of this study showed that partial personal selling, sales promotion, advertising, direct marketing, and public relations have a positive and significant effect on the decision to purchase Daihatsu Xenia cars. Similarly simultaneously these five variables have a positive and significant effect on the purchase decision of Daihatsu Xenia car at PT. Astra Daihatsu international Tbk PalembangKeywords: Personal selling, sales promotion, advertising, direct marketing, public relation.